[R]evolusi Sastra di Era Digital: Perspektif Historis dan Teoretis - Sriastuti, Anna; Inayati, Rif'ah (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
The digital era is a time when almost all areas of life have been assisted by digital technology. It is also interpreted as the emergence of digital technology, which replaces technologies previously used by humans, such as mechanics and electronics analogy. There has been a profusion of digital businesses under the tremendous effect of the internet and digital technology, including cloud computing, virtual reality, mobile devices, and IoTs. The digital age has profound implications for society and the economy since technology is more knowledge-based. In (R)evolusi Sastra di Era Komunikasi Digital: Perspektif Historis dan Teoretis, Ida Rochani Adi, the author, captures the lament of a scientific discipline facing the dilemma of technological change. From a theoretical and historical perspective, this book offers a framework for responding to developments in the digital world of literature, which causes the dynamic understanding of literary works depending on the angle from which the literary work is interpreted. Not only explaining views, thoughts, and theories that have previously developed regarding literary works and criticism, social sciences, humanities, cultural studies, and media, but this book also offers thought, reflection, and development of literary works' ideas in the digital world’s frenetic development.